Knowledge of the Glasgow Coma Scale among Nurses in a Tertiary Hospital in Ghana. (24th June 2019) - Alhassan, Afizu; Fuseini, Abdul-Ganiyu; Musah, Ajara
Abstract : Background . Knowledge of the Glasgow Coma Scale (GCS) is recognized as an asset to all clinical nurses. However, many studies in different countries have reported low levels of knowledge of the GCS among nurses. Little is known about this subject in Ghana. Objectives . The aim of this study was to assess the knowledge of Ghanaian nurses about the Glasgow Coma Scale and identify factors associated with their knowledge. Method . This was a descriptive cross-sectional study involving a convenience sample of 115 nurses from a large teaching hospital in Ghana. We collected data using a structured questionnaire and analysed the data using descriptive statistics, Pearson's correlation, independent samples t-test, and one-way ANOVA. Results . A little more than half of the participants (50.4%) had low knowledge of the GCS as a whole. However, with respect to basic theoretical concepts of the GCS, 62.6% of the participants had good knowledge about it, while only 5.2% demonstrated good knowledge on application of the basic knowledge in clinical scenarios. Working in Neurosurgical ward, female gender, and weekly performance of the GCS were associated with higher levels of knowledge. Academic qualification, years of experience as a nurse, and refresher training on GCS were not associated with knowledge. Conclusion . The findings from this study showed that nurses in Ghana have low levels of knowledge about the GCS. A more structured approach to teaching the GCS that is very thorough and done with demonstrations should be implemented to improve nurses' knowledge on the GCS.